Optimization Of Legal Aid Institution Functions in Regards Nominee Agreement Through Civil Law And Criminal Law Perspektif In Tibubiu-Tabanan Village - I Gusti Agung Ayu Gita Pritayanti Dinar; I Nyoman Gede Sugiartha; Ni Made Puspasutari Ujianti; I Made Ardena; I Kadek Wahyu Dwipayana; Putu Marita Maharani Putri (Fakultas Hukum, Universitas Warmadewa, 2024)
Most villages in Bali have characteristics of